1986
DOI: 10.1149/1.2108450
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Cr in the Passivity of Stainless Steel

Abstract: The nature of passive films formed on 304 stainless steel at +0.25V (vs. SCE) in deaerated solutions of 0.5M H2SO4 and 0.5M H2SO4+0.35M normalNaCl has been determined by RHEED and variable angle XPS. Evidence is given of SO42− and Cl− incorporation into the outer Fe‐rich regions of the passive film. In addition to Cr3+ species which make up the inner layer of the film, CrO42− and CrO3 have been observed by XPS. The mechanism of formation of the Cr6+ species in the solid state and the influence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
136
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(149 citation statements)
references
References 10 publications
12
136
0
1
Order By: Relevance
“…[28][29][30][31][32] Three main depassivation models have been proposed in the presence of aggressive anions. 33 The adsorption model 34,35 is associated with the absorption of aggressive anions on the passive film.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32] Three main depassivation models have been proposed in the presence of aggressive anions. 33 The adsorption model 34,35 is associated with the absorption of aggressive anions on the passive film.…”
Section: Discussionmentioning
confidence: 99%
“…Brooks et al 32 reported the incorporation of sulfate and chromate in the oxide film grown on stainless steel during anodic oxidation in sulfuric acid, and concluded that the incorporation of these anions impeded the ingress of chloride ions into the film. As a consequence of the incorporation of these anions, a coulombic barrier against chloride adsorption is formed, which leads to a high resistance to stable pit formation.…”
Section: Resultsmentioning
confidence: 99%
“…33 In the present work, the anodic oxidation of stainless steel with 1 wt.% H 2 SO 4 might have occurred similarly to the literature. 32,33 In an ethanol/water mixture, the maximum amount of NaCl that can be solubilized is close to 2.0 wt.%, 34 hence in the electrochemical measurements 1.70 wt.% NaCl was added to ensure complete salt dissolution (Table 2). No H 2 SO 4 was added since 1 wt.% of acid decreases the salt solubility in an ethanol/water/NaCl mixture.…”
Section: Resultsmentioning
confidence: 99%
“…27,28 The degradation of a passive film has been discussed using three major models concerning the role of Cl − . (i) The adsorption model 29,30 is associated with the adsorption of Cl − on the passive film surface.…”
Section: Discussionmentioning
confidence: 99%
“…Alloying with Cr forms non-crystalline Cr 2 O 3 on stainless steel by a direct reaction of Cr with H 2 O and improves the resistance to localized corrosion. 2 Alloying with Mo enhances the protectiveness of a passive film to Cl − by increasing oxygen affinity of the stainless steel. 3 Alloying with W inhibits localized corrosion by dissolved WO 4 2− from the passive film to an aqueous electrolyte or by forming insoluble WO 3 , which enhances the stability of the passive film.…”
mentioning
confidence: 99%